Malaysian Secondary School Mathematics Teachers’ Practices in Imparting Mathematical Values - Wan Ali, Wan Zah; Ismail, Habsah; Said Husain, Sharifah Kartini; Ahmad Tarmizi, Rohani; Hamzah, Ramlah; Ismail, Mat Rofa; Konting, Mohd Majid (The International Journal of Learning, 2007)
The purpose of the study is to investigate teachers’ practices in imparting mathematical values during the teaching of mathematics. This research employs a qualitative design where observation and in-depth interview were the main methods used in collecting the data. The informants of the study consist of five secondary school teachers of mathematics who teach in five different schools. The observation data which consist of video recordings and field notes, and interview transcribtions were analysed inductively. The findings showed that majority of the teachers’ instructional practices were inclined towards formalism and logicism. These practices emphasized symbols and formulas in their teaching. However, some elements of Kuhnism were also identified in their practices.